2012
DOI: 10.1007/s00253-011-3774-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of 2,3-butanediol by engineered Bacillus subtilis

Abstract: Production of 2,3-butanediol by Bacillus subtilis takes place in late-log or stationary phase, depending on the expression of bdhA gene encoding acetoin reductase, which converts acetoin to 2,3-butanediol. The present work focuses on the development of a strain of B. subtilis for enhanced production of 2,3-butanediol in early log phase of growth cycle. For this, the bdhA gene was expressed under the control of P( alsSD ) promoter of AlsSD operon for acetoin fermentation which served the substrate for 2,3-butan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…For biological production of 2,3-BDO using renewable biomass, many microorganisms such as Klebsiella, Enterobacter, Acetobactor, Bacillus and Serratia species were isolated [3], and Klebsiella oxytoca, Enterobacter aerogenes, Escherichia coli and Bacillus subtilis were genetically engineered to modulate the metabolic pathways related to 2,3-BDO production [4][5][6][7]. As a feedstock, glucose, sucrose, crude glycerol, molasses, corn, and whey permeate and hydrolysates of cellulosic and non-cellulosic (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For biological production of 2,3-BDO using renewable biomass, many microorganisms such as Klebsiella, Enterobacter, Acetobactor, Bacillus and Serratia species were isolated [3], and Klebsiella oxytoca, Enterobacter aerogenes, Escherichia coli and Bacillus subtilis were genetically engineered to modulate the metabolic pathways related to 2,3-BDO production [4][5][6][7]. As a feedstock, glucose, sucrose, crude glycerol, molasses, corn, and whey permeate and hydrolysates of cellulosic and non-cellulosic (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining acetoin could block the reverse reaction that would transform the 2.3-butanediol back to acetoin. It has been reported that the presence of acetic acid leads to an increased production of 2.3-butanediol by B. subtilis [19]. In contrast, B. licheniformis is able to utilize acetoin but also 2.3-butanediol entirely (data not shown), which might also have contributed to an increase of biomass.…”
Section: Discussionmentioning
confidence: 81%
“…During the fermentation process, pyruvate produced from the glycolytic pathway was converted into α-acetolactate by α-acetolactate synthase (α-ALS) (Biswas et al 2012). The majority of α-acetolactate was subsequently transformed into ( 3R )-AC catalyzed by α -acetolactate decarboxylase (α-ALDC), while a small amount of α-acetolactate was transformed into diacetyl (DA), by the non-enzymatic oxidation decarboxylation (Liu et al 2011b; Yang et al 2014), and DA could be further converted into ( 3S )-AC which decreased the stereoisomeric purity of ( 3R )-AC.…”
Section: Introductionmentioning
confidence: 99%